Influence of pollen emission and weather-related factors on variations in holm-oak (Quercus ilex subsp. ballota) acorn production (Environmental and Experimental Botany, 2007)
In Iberian Mediterranean ecosystems holm-oak acorn production is of vital ecological and economic importance. Economically these fruits are the major component in the feeding systems of high-quality domestic pigs. As in most Quercus species, the chief feature of holm-oak acorn production is its high variability among individuals and years. Many hypotheses have been put forward to explain these ﬂuctuations, but the variables inﬂuencing this alternating behavior remain unknown. From 1998 to 2003 we studied ﬂoral phenology, fruit production, fruit size, airborne pollen emission and meteorology in a holm-oak natural area of South Spain. The results obtained by using a Principal Components Factorial Analysis indicated that pollen emission, up to the day where maximum pollen data are recorded, was the most important factor determining ﬁnal acorn harvest. With regard to the inﬂuence of the weather, temperature, relative humidity and rainfall of January, March and September were the most inﬂuencing variables. Our results support the “wind pollination” hypothesis proposed by other authors in some North-American Quercus studies. Integration of aerobiological, ﬁeld phenological and meteorological data could represent an important step forward in forest fruit production research.